Three new species of Hemiosus Sharp (Coleoptera: Hydrophilidae) and new state records of Hemiosus fittkaui Oliva and H. moreirai dOrchymont from Brazil - Clarkson, Bruno; Ferreira Jr., Nelson (Zootaxa, 2009)
Three new species of Hemiosus (Coleoptera: Hydrophilidae) from Southeastern Brazil are described and illustrated: H. ater sp. nov., H. frades sp. nov., and H. santosi sp. nov. Hemiosus fittkaui Oliva and H. moreirai d’Orchymont are recorded for the first time from Bahia and São Paulo states in Brazil respectively.